IMPLEMENTASI KEBIJAKAN SISTEM ZONASI PPDB DI SEKOLAH MENENGAH PERTAMA NEGERI 3 KRIAN KABUPATEN SIDOARJO - Novinda Dwi Setiawati; Tjitjik Rahaju (Universitas Negeri Surabaya, 2022)
PPDB zoning policy in the education system is a concept to improve services and improve the quality of education in Indonesia which is considered discrimination and favorite school labels still occur, guided by Permendikbud Number. 01 of 2021. This research was conducted to answer problems related to PPDB zoning system policies using qualitative with a descriptive approach that focuses on the implementation of PPDB zoning system policies. The subjects of this research are the Principal, Student Affairs Section, and Teacher who became the committee and responsible for the acceptance of students in SMP Negeri 3 Krian. Data collection techniques come from primary sources, namely interview results and secondary data from relevant literature. The results of the PPDB zoning system study went very well in accordance with the regulations but there are still obstacles and challenges that are related to the perception of parents in understanding the ppdb zoning system policy. Efforts to overcome the problem, namely the school conveys using perception in accordance with applicable regulations.